Applying Response Surface Methodology to Phenolic Compounds from Arbutus unedo: Case Studies with Ultrasound and Dynamic Maceration Extraction - Pedrosa, Mariana C. (2022)
Arbutus unedo L. is a small Mediterranean plant, being fgound mostly in southern Europe, north eastern Africa, Ireland, Palestine and the Canary Islands, and have been studied for its chemical composition.